Integrating Indigenous healing practices within collaborative care models in primary healthcare in Canada: a rapid scoping review - Ginny Brunton; Pierre Côté; Silvano Mior; Hainan Yu; Anne Taylor-Vaisey; Melissa Corso; Astrid DeSouza; Carolina Cancelliere; Kathy MacLeod-Beaver (BMJ Open)
Objectives In November 2020, a series of reports, In Plain Sight, described widespread Indigenous-specific stereotyping, racism and discrimination limiting access to medical treatment and negatively impacting the health and wellness of Indigenous Peoples in British Columbia, Canada. To address the health inequalities experienced by Indigenous peoples, Indigenous healing practices must be integrated within the delivery of care. This rapid scoping review aimed to identify and synthesise strategies used to integrate Indigenous healing practices within collaborative care models available in community-based primary healthcare, delivered by regulated health professionals in Canada.Eligibility criteria We included quantitative, qualitative and mixed-methods studies conducted in community-based primary healthcare practices that used strategies to integrate Indigenous healing practices within collaborative care models.Sources of evidence We searched MEDLINE, Embase, Indigenous Studies Portal, Informit Indigenous Collection and Native Health Database for studies published from 2015 to 2021.Charting methods Our data extraction used three frameworks to categorise the findings. These frameworks defined elements of integrated healthcare (ie, functional, organisational, normative and professional), culturally appropriate primary healthcare and the extent of community engagement. We narratively summarised the included study characteristics.Results We identified 2573 citations and included 31 in our review. Thirty-nine per cent of reported strategies used functional integration (n=12), 26% organisational (n=8), 19% normative (n=6) and 16% professional (n=5). Eighteen studies (58%) integrated all characteristics of culturally appropriate Indigenous healing practices into primary healthcare. Twenty-four studies (77%) involved Indigenous leadership or collaboration at each phase of the study and, seven (23%) included consultation only or the level of engagement was unclear.Conclusions We found that collaborative and Indigenous-led strategies were more likely to facilitate and implement the integration of Indigenous healing practices. Commonalities across strategies included community engagement, elder support or Indigenous ceremony or traditions. However, we did not evaluate the effectiveness of these strategies.